BIOSTRATIGRAPHY OF THE VENDIAN-CAMBRIAN BEDS AND THE LOWER CAMBRIAN BOUNDARY IN SIBERIA - Khomentovsky V.V.; Karlova G.A. (My University, 1993)
General agreement exists that the position of the base of the Cambrian (Precambrian–Cambrian boundary) should coincide with a biostratigraphic marker that can be widely traced and is linked to the evolution of the small shelly fauna. On the Siberian platform the presence of distinct facies during the Vendian–Cambrian interval has made biostratigraphic correlation based on palaeontological data highly contentious. A solution to this problem appears to exist with the recognition of an almost uninterrupted profile in the Aldan–Uchur watershed where key sections expose the eastern and transitional facial region. On this basis we present a general biostratigraphic scheme for the Vendian–Cambrian across the southern Siberian platform that connects separate facies. Further correlation with key sections in northern Siberia leads to the recognition of three biostratigraphic zones for the Vendian–Cambrian interval. These are: Anabarites trisulcatus Zone; Purella antiqua Zone; Aldanocyathus sunnaginicus Zone. The abundance of Chinese-type small shelly fossils in the region of the eastern facies suggest correlation of the A. sunnaginicus Zone with the Siphogonuchites–Paragloborilus Zone of China, and the P. antiqua Zone with the Circotheca–Anabarites–Protohertzina Zone. In places, at the base of the Circotheca–Anabarites–Protohertzina Zone in China, analogies to the A. trisulcatus Zone can be identified. It is proposed that in Siberia the base of the A. sunnaginicus Zone (= base of Tommotian Stage) be taken as the base of the Cambrian. This would correspond with Marker B of the Meishucunian in China
Keywords: Vendian; Cambrian; Докембрий::Протерозой::Неопротерозойская::Вендский; Paleozoic::Cambrian; Precambrian::Proterozoic::Neoproterozoic::Vendian; Палеозой::Кембрийская